Pengujian Sistem Informasi Parkir PT KISP Berbasis Desktop dengan Metode Black-Box - Ilham, Aldi Arista; Azmi, Ammar; Ramadhani, Ardian Rizky; Abeda Falah, Dimas Fatkhi; Saifudin, Aries (Teknik Informatika Universitas Pamulang, 2021)
PT KISP is a market in the Ciledug area, which requires a parking application, it is hoped that this parking implementation can solve the problem of user needs, namely helping the parking system to be more effective and efficient in terms of processing data and information. With this application, it is hoped that it will make it easier for users to make transactions that are easy and in a short time. To design and implement a reliable parking application that is protected from damage or errors, comprehensive testing is needed, such as the functional test, performance test and user interface test aspects, so testing is needed. Testing parking applications based on black box, software testing is useful to ensure whether the actual results match the expected results and to ensure the application is not damaged. Based on the black box testing that has been carried out, it includes input, process and output in the parking application.